The Creighton Century, 1907-2007 - Bates, David; Wallis, Jennifer; Winters, Jane (IHR Conference Series, 2020)
The Creighton Century, 1907-2007 offers a selection of ten lectures from the first 100 years of the University of London's prestigious Creighton Lecture series. Each of the chosen lectures, delivered between 1913 and 2004, is introduced and set in context by a historian of the modern-day University. The collection also includes, and is introduced by, Robert Evans's 2007 centenary lecture, 'The Creighton century: British historians and Europe, 1907-2007'. This volume provides a fascinating insight into the development of the discipline of history over the twentieth and early twenty-first century, revealing some significant changes in approach and emphasis as well as some surprising continuities. The Creighton Century is an invaluable guide to students of historiography, and a chance to revisit some of the great lectures from the series, including those by R. H. Tawney, Lucy Sutherland, Donald Coleman, Eric Hobsbawm and Keith Thomas, published here with commentaries by Virginia Berridge, Justin Champion, Julian Hoppit and Jinty Nelson among others. First published in 2009, The Creighton Century is now reissued as an open access edition by the University of London Press. This edition includes a new joint foreword by the volume's editor, David Bates, and the current director of the Institute of Historical Research, Jo Fox.